The African Union's role in peacekeeping : building on lessons learned from security operations - Badmus, Isiaka A, 1967- (Rethinking peace and conflict studies, 2015)
"This study examines the African Union's (AU) role as a conflict management and peace consolidation actor in Africa. Based on a qualitative research methodology, it analyses AU peace operations in Burundi and Somalia, and hybrid peacekeeping in Darfur, in order to identify the lessons learned and suggest how future outcomes may be improved. Dr Isiaka Badmus discusses the need for African leaders to fully engage and contribute to funding Africa's new security architecture, while continuing to recognise the immediate imperative of international assistance. His study is a significant contribution to the growing body of policy analysis and academic scholarship on peacekeeping in Africa at a time when the AU is developing its capacity for comprehensive and self-sufficient peace support operations"--